Beyond the veil: reflexive studies of death and dying - Thamann, Aubrey; Christodoulaki, Kalliopi M. (Berghahn, 2021)
"Looking at the cultural responses to death and dying, this collection explores the emotional aspects that death provokes in humans, whether it is disgust, fear, awe, sadness, anger, or even joy. Whereas most studies of death and dying treat the subject from an objective viewpoint, the scholars in this collection recognize their inherent connection with death which allows for a new and more personal form of study. More broadly, this collection suggests a new paradigm in the study of death and dying"--